Novel degradation products of argatroban: Isolation, synthesis and extensive characterization using NMR and LC-PDA-MS/Q-TOF - Vinodh Guvvala; Venkatesan Chidambaram Subramanian; Jaya Shree Anireddy; Mahesh Konda (Elsevier, 2018)
Forced degradation study of argatroban under conditions of hydrolysis (neutral, acidic and alkaline), oxidation, photolysis and thermal stress, as suggested in the ICH Q1A (R2), was accomplished. The drug showed significant degradation under hydrolysis (acidic, alkaline) and oxidation (peroxide stress) conditions. The drug remained stable under thermal and photolytic stress conditions. In total, seven novel degradation products (DP-1 to DP-7) were found under diverse conditions, which were not reported earlier. The chemical structures of these degradation products were characterized by 1H NMR, 13C NMR, 2D NMR, Q-TOF-MSn and IR spectral analysis and the proposed degradation products structures were further confirmed by the individual synthesis. Keywords: Argatroban, Forced degradation, NMR, LC-PDA, LC-MS/Q-TOF-MSn